Non-linear robot control: Method of exact linearization and decoupling by state feedback and alternative control design methods - Müller, Peter C. (Zielona Góra: Uniwersytet Zielonogórski)
The dynamics of robots has to be considered as non-linear because of the couplings between the robot axes and the effects of the Coulomb friction within the joints. For the first type of non-linearities a state feedback control is often designed by the method of exact linearization and non-linear decoupling.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka